2016
DOI: 10.1007/s00216-015-9264-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for ferritin as dominant iron-bearing species in the rhizobacterium Azospirillum brasilense Sp7 provided by low-temperature/in-field Mössbauer spectroscopy

Abstract: For the ubiquitous diazotrophic rhizobacterium Azospirillum brasilense, which has been attracting the attention of researchers worldwide for the last 35 years owing to its significant agrobiotechnological and phytostimulating potential, the data on iron acquisition and its chemical speciation in cells are scarce. In this work, for the first time for azospirilla, low-temperature (at 80 K, 5 K, as well as at 2 K without and with an external magnetic field of 5 T) transmission Mössbauer spectroscopic studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Similarly, wild-type Sp7 A. brasilense bacteria reared under the same conditions reduced 22% of the assimilated Fe 3+ -to-Fe 2+ [ 50 ]. These Mössbauer studies suggested that cellular Fe 3+ was stored in ferritin-like components which was verified in other work [ 49 , 51 ]. Furthermore, these studies showed that Fe 2+ existed in highly coordinated forms [ 48 , 50 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, wild-type Sp7 A. brasilense bacteria reared under the same conditions reduced 22% of the assimilated Fe 3+ -to-Fe 2+ [ 50 ]. These Mössbauer studies suggested that cellular Fe 3+ was stored in ferritin-like components which was verified in other work [ 49 , 51 ]. Furthermore, these studies showed that Fe 2+ existed in highly coordinated forms [ 48 , 50 ].…”
Section: Resultssupporting
confidence: 80%
“…Upon surveying the early literature that addressed metal nutrient uptake and metabolic transformation within live cells of rhizospheric microorganisms, and particularly Azospirilla , we found the number of published works scarce [ 43 , 44 , 45 , 46 ]. It was not until later applications of Mössbauer spectroscopy (reviewed in [ 47 ]) that a greater understanding of microbial demands for iron came to light [ 48 , 49 , 50 , 51 , 52 ]. In this collection, studies using wild-type Sp245 A. brasilense grown aeroponically in cultures containing 57 Fe 3+ -nitrilotriacetate complex showed that live cells reduced 33% of the assimilated Fe 3+ -to-Fe 2+ over an 18 h period of growth [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…By using glutamine synthetase isolated from A. brasilense Sp245 cells as an example, the possibility of applying nuclear gamma resonance spectroscopy ( 57 Co nuclei) to the examination of the structural organization of metal cation binding sites in active centers of enzymes was shown . For the first time in relation to Azospirillum bacteria, the assimilation of iron and the composition and structure of iron-containing cellular components were studied (Kovács et al, 2016), and so were the interaction and metabolic transformations of cobalt ions by A. brasilense cultures .…”
Section: Collection Of Rhizosphere Microorganismsmentioning
confidence: 99%
“…If the bearing friction torque is too large, the temperature of the bearing will increase significantly, the lubrication performance of non-circulating grease will be greatly reduced, relative thermal displacement will occur inside the bearing components, and it is easy to cause surface burns on internal components, leading to bearing failure, damage, or even premature scrapping [8][9][10][11][12][13]. The temperature of the bearing has a significant impact on its service life and flexibility, and the deformation of components caused by friction factors also seriously affects the accuracy and stability of machined parts [14][15][16][17][18][19][20]. Therefore, it is more important to analyze the temperature field of bearings in high-speed electric spindle machining applications.…”
Section: Introductionmentioning
confidence: 99%